Padrões ecológicos e evolutivos em lagartos da família Gymnophthalmidae - Oliveira, Bruno Halluan Soares (2021)
The Gymnophthalmidae family is a family of Neotropical lizards with diverse habitats and habits. Although studies involving this family have been growing on last years, these focus on taxonomic studies and phylogenetic proposals, making it necessary still to understand many ecological and evolutionary aspects of the family, as well as the elucidation of several factors that may interfere in these aspects. Thus, this work tested a series of phylogenetic comparative hypotheses in order to evaluate the ecological and evolutionary patterns found in this lizard family. To this end, we collect biological and ecological data from various species of gymnophthalmids through field expeditions, conducted in last years, data from specimens deposited in scientific collections and data available in the literature. From these data, we draw a historical panorama of the ancestral characteristics and verify which characteristics most influence the diversification of the family. Our results showed that the subfamily Cercosaurinae is mainly responsible for the high diversification rates of the group, and this diversification is mainly associated with lower temperature and precipitation environments. In addition, our results also suggest that diversification is related to narrow niche bands, assuming that niche specialization may be one of the factors that also drive diversification in Gymnophthalmidae. The trophic patterns adopted by the family have a mainly historical influence, indicating a conservation in the diet, especially regarding the consumption of larvae, ants and beetles. However, some prey types like cockroaches, termites, and larvae are more closely associated with the environmental factors in which each prey is often found, indicating species opportunism. We also found a relationship between the breadth of the trophic niche and fossoriality, indicating that fossorial species have smaller niche amplitudes than non-fossorial species. The life history traits of the family also have great historical influence, showing that many of the reproductive traits of the family are conserved phylogenetically. Thus, some reproductive strategies are adopted by the species in order to increase reproductive success, like the production of clutch with larger masses in warmer and wetter environments, like rainforests, and the production of multiple clutches in low-temperature locations.